2009
DOI: 10.1074/jbc.m109.020024
|View full text |Cite
|
Sign up to set email alerts
|

Aquifex aeolicus tRNA (N2,N2-Guanine)-dimethyltransferase (Trm1) Catalyzes Transfer of Methyl Groups Not Only to Guanine 26 but Also to Guanine 27 in tRNA

Abstract: In vitro methyl transfer assay revealed that the protein has a strong tRNA methyltransferase activity. We confirmed that this gene product is expressed in living A. aeolicus cells and that the enzymatic activity exists in cell extract. By preparing 22 tRNA transcripts and testing their methyl group acceptance activities, it was demonstrated that this Trm1 protein has a novel tRNA specificity. Mass spectrometry analysis revealed that it catalyzes methyl transfers not only to G26 but also to G27 in substrate tRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
72
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 58 publications
0
72
0
Order By: Relevance
“…Sequencing data revealed the presence of m 2 2 G26 and m 2 G/m 2 2 G27 in tRNA Cys of the hyperthermophilic bacterium A. aeolicus. A single MTase of the Trm1 family is responsible for these modifications (Awai et al 2009). Intriguingly, m 2 G at position 6 has been found in only one bacterial tRNA: tRNA Phe of the extreme thermophilic bacterium T. thermophilus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequencing data revealed the presence of m 2 2 G26 and m 2 G/m 2 2 G27 in tRNA Cys of the hyperthermophilic bacterium A. aeolicus. A single MTase of the Trm1 family is responsible for these modifications (Awai et al 2009). Intriguingly, m 2 G at position 6 has been found in only one bacterial tRNA: tRNA Phe of the extreme thermophilic bacterium T. thermophilus.…”
Section: Discussionmentioning
confidence: 99%
“…The Pf Trm1 enzyme needs specific base-pairing in the D-loop, limited size of the variable loop, and a correct overall tRNA folding for N 2 ,N 2 -dimethylation of G26 (Constantinesco et al 1999). Although initially thought as being excluded from Bacteria, a Trm1 ortholog has been found in the hyperthermophilic bacterium Aquifex aeolicus (Takeda et al 2002;Awai et al 2009). Besides formation of m 2 2 G26, the bacterial Trm1 can also catalyze m 2 G27 formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, S. cerevisiae Trm7 protein catalyzes 2Ј-O-methylation of nucleotides at positions 32 and 34 (25). As described above, we previously reported that A. aeolicus Trm1 has a multisite specificity (21). Although these examples have been reported, there is little knowledge concerning the mechanism of multisite recognition.…”
mentioning
confidence: 95%
“…The responsible gene was first determined to be trm1 from Saccharomyces cerevisiae (13,14) and then experimentally identified from various eukaryotes (Schizosaccharomyces pombe (15), Caenorhabditis elegans (16), and human (17)) and archaea (Pyrococcus furiosus (18), Pyrococcus horikoshii (19), and Haloferax volcanii (20)), consistent with the distribution of the m 2 2 G26 (or m 2 G26) modification in tRNA. Furthermore, we have recently reported that Aquifex aeolicus, a hyper-thermophilic eubacterium, has a Trm1 protein that catalyzes methyl transfer not only to G26 but also to G27 (21).…”
mentioning
confidence: 99%